Numerical aero-thermal study of high-pressure turbine nozzle guide vane: effects of inflow conditions - Phan, HM; Duan, PH; Dinh, CT (American Institute of Physics, 2020)
Accurate predictability of high-pressure turbine nozzle guide vane aero-thermal performance is highly desired in the development campaign due to the exposure of the component to a frequent and high heat load. In this paper, the representative vane profile in modern aero-engines is numerically studied. Aerodynamics and aero-thermal validations of the blade profile have been performed in comparison with the available experimental data. It has been shown that a satisfactory agreement could be achieved with the use of the transitional turbulence model shear stress transport γ–θ due to its superiority in capturing the laminar–turbulent transition. Sensitivity studies on the increase in the inlet turbulence intensity, inlet endwall boundary layer thickness, and inlet total temperature profile have been performed to understand the impact of inflow conditions’ uncertainty on the aero-thermal predictability. Increasing the inlet turbulence intensity increases the pressure surface heat transfer coefficient and induces an earlier transition onset on the suction surface. Due to the rapid decay of turbulence intensity in the numerical model, the use of an artificially high inlet turbulence intensity has been shown to be effective in the prediction improvement. On the other hand, the change in the inlet boundary layer thickness influences the formation and strength of the secondary flow, namely, horseshoe vortex and passage vortex. These secondary flow phenomena affect the local blade surface heat transfer coefficient in the near-endwall region although the most significant rise in heat transfer is found on the endwall. The temperature distortion amplitude of a hot streak and its relative clocking position with the vane significantly affect the heat flux distribution. In contrast, the heat transfer coefficient is less sensitive to the change in hot streak conditions. However, it has been shown that increasing the temperature distortion amplitude could induce a larger difference among different clocking configurations. In addition, decreasing the difference between the fluid and wall temperature would delay the transition onset and stabilize the boundary layer. Further analysis of the unsteady effects has been carried out by comparing the steady and time-averaged flow solutions. It has been observed that the discrepancy between these solutions is attributed to the flow field nonlinearity. Thus, a significant discrepancy can be found in the laminar–turbulent transition as well as in the trailing edge region. However, since the contribution of these regions on the total area-averaged heat transfer is small, their influence on the total vane heat transfer is limited.